Web 2.0: platform for the reconfiguration of education in cyber culture - Marcio Roberto De Lima; Silvania Sousa Do Nascimento (Universidad Politécnica Salesiana, 2013)
This paper discusses cyberculture and new possibilities for teaching and learning offered by the emergence of Web and its evolution to Web 2.0. It relates the principles of cyberculture (Lemos & Levy, 2010; Lemos, 2003; Lemos, 2005) to education. It evidences opportunities and resources for the reconfiguration of pedagogical practice in cyberculture. It proposes that digital devices and communication networks are used with intent to promote learning and citizenship in the digital culture.